2012
DOI: 10.1017/s0007087412000052
|View full text |Cite
|
Sign up to set email alerts
|

States of secrecy: an introduction

Abstract: This introductory article provides an overview of the historiography of scientific secrecy from J.D. Bernal and Robert Merton to this day. It reviews how historians and sociologists of science have explored the role of secrets in commercial and governmentsponsored scientific research through the ages. Whether focusing on the medieval, early modern or modern periods, much of this historiography has conceptualized scientific secrets as valuable intellectual property that helps entrepreneurs and autocratic govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…In many instances, industrial researchers and governments use scientific secrets as an effective tool to manipulate the beliefs of their competitors and the larger public, and not necessarily to protect the knowledge they possess (Vermeir and Margócsy 2012 ).…”
Section: Research Funding Policy Makers and Industrymentioning
confidence: 99%
“…In many instances, industrial researchers and governments use scientific secrets as an effective tool to manipulate the beliefs of their competitors and the larger public, and not necessarily to protect the knowledge they possess (Vermeir and Margócsy 2012 ).…”
Section: Research Funding Policy Makers and Industrymentioning
confidence: 99%
“…Some even argue that it is only with the Méthode de nomenclature chimique (1787) that modern chemistry was born during the 'Chemical Revolution' (Lefèvre, 2018). The long-held opinion that there was a 'Scientific Revolution' in the seventeenth century during which the scientific method emerged and amongst other things, secretive and obscure language in science was replaced by scientific openness is now widely contested within the history of science (Principe, 2011;Vermeir and Margócsy, 2012). The scholarly movement called 'The New Historiography of Alchemy' pioneered by Lawrence Principe and William Newman (Martinón-Torres, 2011) has demonstrated that the caesura between alchemy and chemistry is an artificial one (Newman and Principe, 1998;Newman, 2006).…”
Section: Current Trends In the Historiography Of Alchemymentioning
confidence: 99%
“…La question n'est pas de savoir si cette recette est vraie, fausse, vraie-fausse ou faussevraie. Ce luthier possède quelque chose que les autres n'ont pas, quelque chose qu'il garde secrètement -pas trop quand même, sinon ce secret perdrait son efficacité psychologique et sociale [Vermeir et Margócsy, 2012] -et qu'il est supposé avoir intégré à sa pratique. Et c'est peut-être là que se trouve le vrai secret de Stradivarius : l'idée de l'existence de savoirs tangibles qui confèrent une autre épaisseur aux gestes de ceux qui les ont en leur possession ; même si l'on sait que le savoir n'est pas « une chose en soi » qui pourrait se « transvaser » automatiquement [Sigaut, 1991 : 42] Le faire et le discours sur le savoir-faire ne se confondent pas [Chamoux, 1996].…”
Section: Le (Secret Du) Secret De Stradivariusunclassified